12-3z+2y-4x=0

Simple and best practice solution for 12-3z+2y-4x=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12-3z+2y-4x=0 equation:


Simplifying
12 + -3z + 2y + -4x = 0

Reorder the terms:
12 + -4x + 2y + -3z = 0

Solving
12 + -4x + 2y + -3z = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -4x + 2y + -12 + -3z = 0 + -12

Reorder the terms:
12 + -12 + -4x + 2y + -3z = 0 + -12

Combine like terms: 12 + -12 = 0
0 + -4x + 2y + -3z = 0 + -12
-4x + 2y + -3z = 0 + -12

Combine like terms: 0 + -12 = -12
-4x + 2y + -3z = -12

Add '-2y' to each side of the equation.
-4x + 2y + -2y + -3z = -12 + -2y

Combine like terms: 2y + -2y = 0
-4x + 0 + -3z = -12 + -2y
-4x + -3z = -12 + -2y

Add '3z' to each side of the equation.
-4x + -3z + 3z = -12 + -2y + 3z

Combine like terms: -3z + 3z = 0
-4x + 0 = -12 + -2y + 3z
-4x = -12 + -2y + 3z

Divide each side by '-4'.
x = 3 + 0.5y + -0.75z

Simplifying
x = 3 + 0.5y + -0.75z

See similar equations:

| 6x-2+7x= | | 5x+4/3x=6 | | (x^2)+5x-36=0 | | 5x-8y=-24 | | 5x+3/4x=6 | | 9D-7=7A | | a-2a+5= | | -5(17)+y=13 | | (x^2)-((x^3)/6) | | 4/5x-7x=6 | | 7x(x-3)(x+2)=0 | | 12x+3y=162 | | X/8+2=14 | | m+10-14m=-5 | | (3-3/2y)^2 | | -3x+3(5+13)=3 | | x-3+5x= | | 4k-28k=-49 | | 7x-4/5x=6 | | H/5+3=-6 | | 11(4-6x)+5(13y+1)=9 | | 3x+7-5x= | | 4k-14+3/c=21 | | 5h=2 | | 0=2m-18 | | -0.3f+1.3=4.8 | | -18/y+3 | | (x+16)+(x+22)=231 | | y^2-3y/y+3 | | 5(4x)-1/2x=234 | | 9h+4.5-7h+1.75= | | 6x+3x-3= |

Equations solver categories